Hidden in Plain Sight: Unraveling the Mystery of Hemoptysis - Pranav Ish; Naresh Kumar; Sanchit Mohan; Rohit Kumar; Nipun Malhotra; Vidushi Rathi; Nitesh Gupta (Journal of Advanced Lung Health)
Foreign body aspiration is a common cause of hemoptysis. The exact cause may sometimes be hidden and may not be revealed in chest radiology but may eventually come to light with bronchoscopy and may prevent complications.